2024
DOI: 10.1021/acscatal.3c04811
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Highly Active Pd–Ti3+ Sites in Defective Pd/TiO2 Catalysts for Efficient Hydrogenation of Styrene–Butadiene–Styrene

Shidong Wang,
Bingqing Ge,
Zongxuan Yang
et al.

Abstract: Defect-rich Pd/TiO 2 catalysts are intensively adopted in heterogeneous hydrogenation reactions; however, the complexity of the defect structure makes it difficult to precisely identify which Pd-defect combination dominates the catalytic activity. Herein, defective TiO 2 nanoflakes with tunable ratios of Vo to Ti 3+ defects were synthesized and used to construct Pd−Vo and Pd−Ti 3+ active sites after loading Pd to investigate the role of defects in regulating the structural and catalytic properties of defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that the low valence metal centers of transition metal oxides can serve as active sites for inducing localized electron reduction of N 2 . 15 Recently, Hirakawa et al found that Ti 3+ species in TiO 2 can provide electrons for the anti-bonding π* orbitals of N 2 , which greatly facilitates the breaking of NN bonds. 16 Han et al also demonstrated that the high concentration of Ti 3+ sites in C-TiO x is the main reason for the enhanced N 2 photoreduction activity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the low valence metal centers of transition metal oxides can serve as active sites for inducing localized electron reduction of N 2 . 15 Recently, Hirakawa et al found that Ti 3+ species in TiO 2 can provide electrons for the anti-bonding π* orbitals of N 2 , which greatly facilitates the breaking of NN bonds. 16 Han et al also demonstrated that the high concentration of Ti 3+ sites in C-TiO x is the main reason for the enhanced N 2 photoreduction activity.…”
Section: Introductionmentioning
confidence: 99%